2018
DOI: 10.2147/opth.s186543
|View full text |Cite
|
Sign up to set email alerts
|

How to minimize pterygium recurrence rates: clinical perspectives

Abstract: The main treatment for pterygium is surgical removal. However, pterygium surgery is concerned with high rates of postoperative recurrence. Predicting factors of recurrence are not fully understood, yet, but they probably depend on a multitude of patient-related, clinical, and/or surgical factors. Several adjuvant treatments have been proposed to reduce postoperative pterygium recurrence, including different antimetabolites, antiangiogenetic factors, and radiation therapy. The purpose of this review is to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 166 publications
(167 reference statements)
2
60
0
Order By: Relevance
“…Surgery performed by trainees was associated with borderline significantly higher postoperative recurrence (7.7%), which was consistent with previous studies 8,15 . Previous reported recurrence rate was 3.3-18.5% for experienced surgeons 6 , and 10-82% for trainees 8,15 . The lower recurrence rate in this study can be attributed to two reasons: CAG transplantation has been shown to be superior to bare sclera technique or AMT 4,9,10 , with respect to recurrence, and in all cases we used fibrin glue, which is associated with lower recurrence compared to sutures 38 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Surgery performed by trainees was associated with borderline significantly higher postoperative recurrence (7.7%), which was consistent with previous studies 8,15 . Previous reported recurrence rate was 3.3-18.5% for experienced surgeons 6 , and 10-82% for trainees 8,15 . The lower recurrence rate in this study can be attributed to two reasons: CAG transplantation has been shown to be superior to bare sclera technique or AMT 4,9,10 , with respect to recurrence, and in all cases we used fibrin glue, which is associated with lower recurrence compared to sutures 38 .…”
Section: Discussionmentioning
confidence: 95%
“…The risk of recurrence after pterygium surgery is multifactorial, with patient-attributed factors, such as age, ethnicity, morphology of pterygium 3,6,7 , and surgeon-attributed factors, such as the surgical experiences and techniques 3,8 . A meta-analysis of randomized controlled trials has shown that bare scleral technique increases the risk of postoperative recurrence by 6 to 25 times compared to a tissue grafting technique 9 .…”
mentioning
confidence: 99%
“…This study indicated that there was no difference in recurrence between intra-operative application of MMC or drops and also no statistically difference was found in groups receiving 0.2 mg/ml or 0.4 mg/ml MMC for 3 minutes. Since thenmultiple studies have followed with intra-operative use of MMC in concentration of 0.2 mg/ml or 0.4 mg/ml with application time of 3 -5 minutes 12,13,14 .…”
Section: Pterygium Surgerymentioning
confidence: 99%
“…Pterygium is a common disease of the ocular surface, characterized by invasion of triangular inflammatory fibrovascular lesions into the cornea, which can cause inflammation, irregular corneal astigmatism and stromal opacity (1). Currently, the underlying mechanisms of pterygium have not been well elucidated and surgical excision is the standard treatment; however, pterygium recurrence is common following surgery (2). In order to devise strategies for the non-surgical treatment of pterygium or the prevention of recurrence after resection, it is important to understand the underlying molecular mechanisms of the pathogenesis of pterygium.…”
Section: Introductionmentioning
confidence: 99%